Bone marrow expression of CD68/CD163 macrophages, IL‐17 and FOXP3 cells in aplastic anemia and their relation to prognosis. (16th December 2022) - Vaht, Krista; Brenner, Jonas; Ednersson, Susanne Bram; Ljungman, Per; Brune, Mats; Andersson, Per‐Ola
Abstract: Objectives: The primary mechanism for bone marrow failure in aplastic anemia (AA) is autoimmune hematopoietic stem cell destruction. AA can be cured with antithymocyte globulin (ATG) treatment, and some smaller studies have indicated that the number of regulatory T cells (Tregs) may be predictive of response. Additionally, AA patients appear to have elevated numbers of Th17 cells and bone marrow macrophages, but outcome data are missing. Methods: We performed immunohistochemistry on bone marrow biopsies from 121 ATG‐treated AA patients and 14 healthy controls, using antibodies against FOXP3 (for Tregs), IL‐17 (for Th17), CD68 (for pan‐macrophages) and CD163 (for M2 type macrophages) to study their possible relation to ATG response and AA prognosis. Results: AA patients had significantly fewer Tregs and Th17 cells but significantly more macrophages compared with controls. Treg, Th17 and pan‐macrophage cell numbers were not associated with ATG response or differences in survival. Patients with higher levels of M2 macrophages had improved 5‐year overall survival: 79.6% versus 57.4% ( p = .017), and this benefit was primarily seen in AA patients with non‐severe disease. Conclusions: We found that Treg and Th17 cell numbers did not predict ATG response or survival, whereas M2 macrophages may be associated with improved survival.